Information-Motivation-Behavioral Skill in Diabetes Self-management Using Structural Equation Modeling Analysis - Kurtanty, Dien; Bachtiar, Adang; Candi, Cicilya; Pramesti, Alya; Rahmasari, Almira Fanny (Kesmas, 2023)
Diabetes is the “mother” of various diseases increasing the risk of morbidity and mortality. Diabetes self-management, an effort made by patients to control blood sugar levels, is an important part of the management strategy. Therefore, this study analyzed information, motivation, and behavioral skills associated with diabetes self-management. Data were collected in the Special Capital Region of Jakarta, with 277 diabetic patients selected using a questionnaire by a systematic random sampling method. The analyzed variables were information (with indicator variables of information on physical activity, nutritional intake, drug consumption, and blood sugar monitoring); sociodemographic (age, sex, occupation, education level, and duration of diabetes); motivation (barrier, benefit, self-efficacy, severity, and susceptibility); and behavioral skills (new motor, self-regulatory, and social skills), which were analyzed to identify their influence on diabetes self-management using structural equation modeling. The results indicated that information and motivation significantly and positively affected behavioral skills; while, sociodemographic did not. Behavioral skills had a significant and positive effect on diabetes self-management. Accordingly, people with diabetes information, motivation, and behavioral skills need to be improved to increase the success of diabetes self-management.